(3eTcd EYQGH GdbQBf GdcQjes
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3YWa Ydi GdcGa ai bhdg ceKd GdPi GPgH ai ehVhY QaY NHQ s
(3BNQgG (B:s
(3hdG jLhR YWag Ydi GdLfI dCf GdfGS dG jhShSf ai UOhQ GdfGS EfeG jhShS GdLf adeG GSJMGd GdeYfi MedJg Ydi GdYWa Ydi GdhShGS BNQ cJGH eTcd EYQGH GdbQBf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs